Instilling the Character of Love for the Country Through the Pancasila Strengthening Model in Early Childhood - Hamid Samiaji, Mukhamad; Prawening, Cesilia; Tri Mulyani, Chandra (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Planting character Love homeland since​ early is step strategic in to form generation that has nationalism and love towards Indonesia. In children age early on, the values of Pancasila can applied through a simple approach However impressive, like activity play , stories , and interactions social . Problems regarding the decline attitude nationalism No Can left alone so only. Furthermore, PAUD is considered only For read and write just whereas important apply child - centered and learning projects​ while playing outside​ a class that fosters Pancasila values since age early through interest child. So from that, Research This use methodology qualitative type studies case with technique data collection in the form of observation, interviews, and documentation that describes How to plant Love homeland and nationality through the Pancasila strengthening model for children age early. Research This utilise method Miles and Huberman's interactive data model analysis in the form of data collection, data reduction, data presentation, description, and conclusion Conclusion. Results of the study This put into practice as a model for strengthening Pancasila in children age early, especially character Love homeland and nationality.